Design and optimization of a dual-band slotted microstrip patch antenna using Differential Evolution Algorithm with improved cross polarization characteristics for wireless applications. Issue 11 (24th July 2019) - Kaur, J.; Nitika,; Panwar, R.
ABSTRACT: This work presents a rectangular microstrip-line-fed patch antenna for Long Term Evolution, Universal Mobile Telecommunication Systems, Local Area Network, Bluetooth, Industrial, Scientific and Medical, Wireless Broadband, Worldwide Interoperability for Microwave Access, International Mobile Telecommunication, Radio Frequency Identification and Wireless Fidelity applications. The overall dimensions of antenna are 70 × 70 mm 2 . The antenna consists of a slotted radiating patch and defected ground structure, which is used to achieve dual-band frequency characteristics with appreciable bandwidth satisfying several communication standards simultaneously. Differential Evolution (DE) Algorithm is enforced in this work for achieving the best antenna geometrical design parameters and to obtain the desired results. The proposed antenna covers dual-frequency bands viz. 2.34–2.68 and 5.28–6.32 GHz with their resonating frequencies at 2.53 and 5.77 GHz, respectively. Further, an improvement in cross polarization discrimination of 15.4 dB for E plane and 9 dB for H plane is observed using DE algorithm. The fabrication and measurement of proposed antenna was carried out to verify the simulation results in the succeeding sections.